Purification and characterization of recombinant G16 alpha from Sf9 cells: activation of purified phospholipase C isozymes by G-protein alpha subunits. - Kozasa, T (1993)
A cDNA encoding G16 alpha, the alpha subunit of a heterotrimeric guanine nucleotide-binding protein, was expressed in Sf9 cells using recombinant baculovirus. G16 alpha in membrane extracts of Sf9 cells activated phospholipase C-beta 1 (PLC-beta 1) in the presence of guanosine 5'-[gamma-thio]triphosphate; the system could not be activated by Al3+, Mg2+, and F-. The G16 alpha in the cytosolic fraction of Sf9 cells did not stimulate PLC-beta 1. Concurrent expression of the G-protein beta gamma subunit complex increased the amount of G16 alpha in Sf9 cell membranes. The guanosine 5'-[gamma-thio]triphosphate-activated form of G16 alpha was purified from cholate extracts of membranes from cells expressing G16 alpha, and the G-protein beta 2 and gamma 2 subunits. G16 alpha activated PLC-beta 1, PLC-beta 2, and PLC-beta 3 in a manner essentially indistinguishable from that of Gq alpha. G16 alpha-mediated activation of PLC-beta 1 and PLC-beta 3 greatly exceeded that of PLC-beta 2. G16 alpha did not activate PLC-gamma 1 or PLC-delta 1. Thus, two distantly related members of the Gq alpha family, Gq alpha and G16 alpha, have the same ability to activate the known isoforms of PLC-beta.